Aloin Extract on Histopathological Features of Osteogenesis in Fractures of Rattus Norvegicus Wistar Strains - Abdullah, Dessy; Nurrifdah, Nadilla; Febrianto, Budi Yulhasfi; Vani, Ade Teti; Dewi, Nadia Purnama (Journal La Medihealtico, 2024)
The process of bone repair after trauma or fracture will involve cells, signalling molecules, and processes that have been active during the remodelling process. The new study found that Aloin can promote the expression of osteogenic differentiation regulators, such as Bmp-1 (Bone morphogenetic protein 1) and Runx1 (Runt-related transcription factor 1) in MC3T3–E1 cells, where Runx1 is a transcription factor in osteogenic differentiation—knowing and analyzing aloin extract on the histopathological picture of osteogenesis in Wistar strain rattus norvegicus fractures. This type of research is a laboratory experimental test with a post-test-only control group design. The population number will be divided into four groups, namely positive control group (+), negative control (-), treatment group 1, and treatment group 1, with 14 samples using the Purposive Sampling technique. Univariate data analysis is presented as mean and standard deviation and one-way ANOVA statistical test. Data processing using computerized IBM version 15.0 of the SPSS program. Histopathological picture of osteogenesis in fractures of male rats (Rattus norvegicus) based on osteoblast values at least at K(-), which is 30.64, and K(+), which is 31.90. In the P1 group, the highest average osteoblast value was 39.58, and P1's was 38.14. The osteoclast value is obtained at least at K(-) and 8, and K(+) is 19.01. In the P1 group, the highest average osteoclast value was 16.73, and P1 was 11.70. Aloin extract did not affect the histopathological picture of osteogenesis in fractures of male rats (Rattus norvegicus) with a sig of >0.05.